The relationship between the capital structure and the financial efficiency of the company`s activities - D. V. Voyko; A. V. Voyko (Вестник университета)
Modern approaches to assessing the cost of capital of a company in order to choose the most successful structure are considered. The SARM model for estimating the cost of equity is described in detail. The indicator of economic value added was proposed as a criterion of economic efficiency. Modern approaches to assessing the value of a company are reflected, financial instruments and market indices used to assess the cost of capital of companies are studied. The hypothesis of the relationship between the capital structure and value was also evaluated and confirmed on the example of an operating oil and gas company, taking into account the actual results of its activities and industry characteristics.